Irrigação por gotejamento fotovoltaico autônomo com rastreador solar - Haupenthal, Soni Willian (2022)
Photovoltaic energy enables a new scope for generating clean energy with low maintenance and accessibility to remote places, while the irrigation system enables higher productivity and development for areas with low rainfall. Within the irrigation system, uniformity is one of the leading indicators of the quality of the process. Notably, this parameter is influenced by several factors, among them the topography of the terrain; therefore, so that uniformity is monitored with more excellent qualification, it is essential to use statistical techniques, such as statistical quality control, through control charts, of Shewhart, which enable its monitoring. Thus, the objective of this work was to evaluate the performance of a drip irrigation system with a photovoltaic solar energy supply. The experiment was composed of a photovoltaic module directly connected to the water pump, with discharge conducted to an irrigation system formed by four drip pipes installed on the test bench. The tests were performed with the power supply, using the fixed and solar tracking system, in which the variables under analysis were irradiation, voltage, current, and power; as for the irrigation system, the variables under analysis were the inlet and final pressure, as well as the dripper flow rate. The work was divided into three articles, being that the first article presented with the objectives of evaluating the influence of the use of the photovoltaic tracking system in irrigation uniformity in the winter period, characterized for presenting lower value of photovoltaic energy production. The second article aimed to analyze the influence of solar tracking on drip irrigation in winter and spring periods, trying to identify if the increase of irradiation in the spring period would influence the energy production and, consequently, the irrigation process, as well as if the system remained under statistical quality control over time. Finally, the third article aimed to characterize the influence of dripper pipe inclination and the use of photovoltaic solar tracking under the irrigation process, based on statistical quality control and process capability index. When the photovoltaic solar tracking system was used, the irradiation, current, voltage, and power values were higher, giving higher efficiency for energy production (16.23%) and making the energy generation more stable. The highest average power (155.94 W) and lowest coefficient of variation (19.06%) were found in the spring period using solar tracking. Regarding the different inclinations in drip irrigation, for all treatments under analysis, the uniformity values exceeded 90%, being classified as excellent; it is noteworthy that the highest flows were observed at the beginning of the lines for the hillside and level treatments, while on the slope, the end of the line showed the highest flows. Despite the variability of the power generation, mainly from the fixed PV system, the uniformity coefficients reached the level of excellence in all analyses. Based on the Shewhart control charts, it was possible to define that the presence of clouds and high radiation values affect the irrigation system's power generation, pressure, and flow rate. Thus, it can be concluded that the amplitude in hours in the energy production and the higher stability of the generation when using the tracking system positively influenced the drip irrigation process. However, it should be emphasized that, within the uniformity coefficients, there was no statistical change at 5% probability by the Tukey test. It can also be concluded that, from the capacity index, the distribution uniformity remained under control over time.